2018
DOI: 10.2116/analsci.18sdn01
|View full text |Cite
|
Sign up to set email alerts
|

Array-based Generation of Response Patterns with Common Fluorescent Dyes for Identification of Proteins and Cells

Abstract: A differential array consisting of commercially available common fluorescent dyes was constructed for the identification of proteins and human cancer cells. Fluorescence of dyes was differently altered by mixing with proteins and human cancer cells, generating response patterns that are unique to the analytes. Linear discriminant analysis of the obtained patterns enabled the accurate identification of eight proteins and three human cancer cells. As this system can be easily prepared, it would offer a unique op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We recently reported that a sensor array can be constructed using only readily available materials, i.e., commercially available fluorescent dyes, including fluorescein, rhodamine 6G, and acridine orange. 68 Each fluorescent dye exhibits a different affinity against cell surfaces due to their structural differences (e.g., charge and hydrophobicity). Thus, the array of common fluorescent dyes generates unique response patterns to cells.…”
Section: •3 Tips For the Design Of Easy-to-prepare Sensor Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that a sensor array can be constructed using only readily available materials, i.e., commercially available fluorescent dyes, including fluorescein, rhodamine 6G, and acridine orange. 68 Each fluorescent dye exhibits a different affinity against cell surfaces due to their structural differences (e.g., charge and hydrophobicity). Thus, the array of common fluorescent dyes generates unique response patterns to cells.…”
Section: •3 Tips For the Design Of Easy-to-prepare Sensor Arraysmentioning
confidence: 99%
“…Advance Publication by J-STAGE Received January 15, 2020; Accepted March 30, 2020; Published online on April 3, 2020 DOI: 10.2116/analsci.20R002 from a single probe is one of the easiest ways to increase the number of dimensions of sensing. 50, [64][65][66]68 For a greater response, additional components can be further added to the reaction vessels or wells of the array. An innovative approach to efficiently double the pattern information using additives has been proposed by Rotello and co-workers.…”
Section: Analytical Sciencesmentioning
confidence: 99%
“…In the field of analytical chemistry, discriminant analysis based on not only conventional LDA but also the advanced algorithms have been reported in many kinds of samples, e.g., DNA, 26 phospholipids, 118 cancer cells, 119 etc.…”
Section: Classificationmentioning
confidence: 99%